2023
DOI: 10.1017/s0954579423000317
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and reactive aggression: Developmental trajectories and longitudinal associations with callous–unemotional traits, impulsivity, and internalizing emotions

Abstract: Research on proactive and reactive aggression has identified covariates unique to each function of aggression, but hypothesized correlates have often not been tested with consideration of developmental changes in or the overlap between the types of aggression. The present study examines the unique developmental trajectories of proactive and reactive aggression over adolescence and young adulthood and tests these trajectories’ associations with key covariates: callous–unemotional (CU) traits, impulsivity, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…The present study found that fear reactivity, both conscious and automatic, played a unique role in the interplay between CU traits and aggression subtypes. In line with past research, we found CU traits were not associated with reactive aggression [36][37][38], but greater automatic fear reactivity (higher SCR) was linked to reactive aggression [35]. Furthermore, greater automatic fear reactivity (higher SCR) moderated the link between high CU traits and high reactive aggression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study found that fear reactivity, both conscious and automatic, played a unique role in the interplay between CU traits and aggression subtypes. In line with past research, we found CU traits were not associated with reactive aggression [36][37][38], but greater automatic fear reactivity (higher SCR) was linked to reactive aggression [35]. Furthermore, greater automatic fear reactivity (higher SCR) moderated the link between high CU traits and high reactive aggression.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the relation between CU traits and reactive aggression is when youth with CU traits have hyperactive automatic threat processes. This may explain the mixed findings of some research linking CU traits to reactive aggression, while others do not [36][37][38]. This may suggest that CU trait-related reactive aggression is more automatic and driven by a physiological response than a conscious response to a threat.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moderate-sized (0.47) reductions in teacher-rated proactive aggression over a long-term three-year follow-up were found in a study that compared CP with typical school services with 241 elementary school boys and girls. Intervention effects in this follow-up study and another 6-year follow-up study [8], were also found on stable callous-unemotional traits, which were associated with proactive aggression in longitudinal research [22].…”
Section: Proactive and Reactive Aggressionsupporting
confidence: 60%
“…Longitudinal research has provided evidence suggesting that proactive and reactive aggression are unique constructs with separate developmental trajectories and distinct associated factors. 8 Identifying the risk and protective factors of both types of aggressive behavior during adolescence is crucial in recognizing the emergence and cessation of aggression, thereby informs effective intervention and prevention strategies. Recently, abundant evidence has emphasized the significance of parental attachment in shaping aggressive behaviors.…”
Section: Introductionmentioning
confidence: 99%